Before Brown : Civil Rights and White Backlash in the Modern South - Feldman, Glenn (Book collections on Project MUSE., 2004)
Detailing the ferment in civil rights that took place across the South before the momentous Brown vs. Board of Education decision in 1954, this collection refutes the notion that the movement began with the Supreme Court decision, and suggests, rather, that the movement originated in the 1930s and earlier, spurred by the Great Depression and, later, World War II.